The Competence of Teacher Assistants in the Context of Working with Visually Impaired Students. Needs of the Environment and the Vision of Change - Paplińska, Małgorzata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The text contains an analysis of the competence of a special education teacher, with particular emphasis on the competence of one working as a teacher assistant with blind and visually impaired students. It attempts to answer the question of what competence a teacher assistant should have. On the one hand, this competence must be a response to the current needs of students with visual impairments, their teachers and parents. In line with the current approach to inclusive education, the teacher assistant who works with visually impaired students should be equipped with a whole array of competences, especially a number of highly specialised ones. On the other hand, taking into account e.g. creative and ethical competences, universities educating future teachers of the kind are not able to equip graduates with full competences.